2014
DOI: 10.1111/pcn.12138
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex and cerebellar hemisphere neurometabolite changes in depression treatment: A 1H magnetic resonance spectroscopy study

Abstract: Aim:We utilized single-voxel 1 H magnetic resonance spectroscopy to determine biochemical abnormalities related to major depressive disorder (MDD) in the bilateral dorsolateral prefrontal cortex, anterior cingulate cortex (ACC), and cerebellar hemisphere before and after antidepressant treatment. Methods:Fifteen adult MDD patients and 15 ageand sex-matched healthy controls were involved. Magnetic resonance spectroscopy of the brain was conducted in all subjects at the beginning of the study and the depressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 36 publications
2
54
0
2
Order By: Relevance
“…In neuro-inflammatory conditions, elevated myo-Inositol levels are presumed to reflect astrocyte and microglial activation (Chang et al, 2014, Kirov et al, 2013; conversely, reduced myo-Inositol levels have been interpreted as evidence of astrocyte necrosis in neuromyelitis optica (Ciccarelli et al, 2013). Several postmortem studies have found reduced density of glial cells (Ongür et al, 1998;Hamidi et al, 2004) and decreased concentration of protein markers specific to astrocytes in MDD (MiguelHidalgo et al, 2000;Miguel-Hidalgo et al, 2011;MiguelHidalgo et al, 2014), providing a histological basis for interpreting reduced myo-Inositol levels in MDD as evidence of glial dysfunction (Coupland et al, 2005;Chen et al, 2014). Analysis of post-mortem tissue has also implicated reduction in glial numbers in schizophrenia (Rajkowska et al, 2002;Stark et al, 2004), though MRS studies, including this current study, have generally found no evidence of altered levels of myo-Inositol in schizophrenia Schwerk et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In neuro-inflammatory conditions, elevated myo-Inositol levels are presumed to reflect astrocyte and microglial activation (Chang et al, 2014, Kirov et al, 2013; conversely, reduced myo-Inositol levels have been interpreted as evidence of astrocyte necrosis in neuromyelitis optica (Ciccarelli et al, 2013). Several postmortem studies have found reduced density of glial cells (Ongür et al, 1998;Hamidi et al, 2004) and decreased concentration of protein markers specific to astrocytes in MDD (MiguelHidalgo et al, 2000;Miguel-Hidalgo et al, 2011;MiguelHidalgo et al, 2014), providing a histological basis for interpreting reduced myo-Inositol levels in MDD as evidence of glial dysfunction (Coupland et al, 2005;Chen et al, 2014). Analysis of post-mortem tissue has also implicated reduction in glial numbers in schizophrenia (Rajkowska et al, 2002;Stark et al, 2004), though MRS studies, including this current study, have generally found no evidence of altered levels of myo-Inositol in schizophrenia Schwerk et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Consistently, proton magnetic resonance imaging ( 1 H-MRS) studies of patients with major depressive disorder (MDD) report reduced levels of myo-Insoitol in prefrontal and anterior cingulate cortex (ACC; Frey et al, 1998;Coupland et al, 2005;Chen et al, 2014). Conversely, positive clinical outcome in MDD is associated with increased myo-Inositol levels (Chen et al, 2014;Zheng et al, 2010). These data indicate that reduced myo-Inositol in MDD is primarily associated with depression symptoms rather than being secondary to treatment.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…On the contrary, bipolar disorder may be characterized by elevated frontal cortex mI concentrations, and the anti-manic effects of lithium may be associated with a reduction of mI [61]. Electro-convulsive treatment (ECT) may increase mI concentrations [60]. These results are not, however, unanimous, as some studies have reported increased or similar mI levels in depressed patients versus healthy controls [24,62,63].…”
Section: Discussionmentioning
confidence: 50%
“…It has been suggested that a reduced cerebral mI concentration is a neurochemical biomarker for depression; lower inositol has been reported in the cerebrospinal fluid of depressed patients [56] as well as in the frontal cortex of suicide victims (postmortem) and patients with bipolar disorder [57]. Some 1 H MRS studies have observed lower cerebral mI concentrations in depressed patients than in controls [48,58,59,60]. On the contrary, bipolar disorder may be characterized by elevated frontal cortex mI concentrations, and the anti-manic effects of lithium may be associated with a reduction of mI [61].…”
Section: Discussionmentioning
confidence: 99%